Development and Evaluation of Naproxen Sodium Gel Using Piper cubeba for Enhanced Transdermal Drug Delivery and Therapeutic Facilitation - Patwardhan, Sunetra; Patil, Manohar; Sockalingam, Anbazhagan (Recent Patents on Drug Delivery & Formulation, 2017)
Background: The absorption of drug through skin avoids many side effects of oral route like gastric irritation, nausea, systemic toxicity etc and thus improves patient compliance. Naproxen sodium (NPRS) is one of the potent NSAID agents. Objective: The present study was aimed to develop and evaluate the gel formulation containing NPRS for transdermal drug delivery reducing the side effects and improving patient compliance. The patents on topical delivery of NSAIDS (US 9012402 B1, US 9072659 B2, US 20150258196 A1) and patents indicating use of herbal penetration enhancers (US 20100273746A1, WO 2005009510 A2, US 6004969 A) helped in selecting the drug, excipients. Method: Current protocol employs various extracts of Piper cubeba fruit to evaluate its role in absorption of NPRS. Various batches containing 1% NPRS and varying concentrations of synthetic permeation enhancers or the extracts were formulated in carbopol gel. Gel was evaluated for parameters like organoleptic parameters, pH, viscosity and spreadability. An ex-vivo percutaneous absorption of NPRS from gel was investigated and compared with best performing synthetic enhancer, transcutol P (TP). Result: The batch containing 2% n-hexane extract (NHE) of Piper cubeba showed higher permeation than TP and Chloroform (CE), Methanolic (ME) and aqueous (AE) extracts as well. It showed improved % cumulative release (85.09%) and flux (278.61μg/cm2.h), as compared to TP and other extracts. Histopathology indicated the formulation safer as compared to that with synthetic enhancer. Conclusion: It suggests P. cubeba as effective and safer tool for transdermal delivery and acts as therapeutic facilitator for naproxen. GC-MS analysis indicates lignans & terpenes in NHE to which this permeation enhancement activity may be attributed.
Keywords: cumulative release